DESKRIPSI KESULITAN BELAJAR SISWA PADA MATERI PROTISTA KELAS X SMA NEGERI 1 KEMBAYAN - Riki, Ajustus; Ningsih, Kurnia; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of this study was to investigate students’ difficulty, level of learning difficulties and factors causing students’ learning difficulties in protist at SMAN 1 Kembayan. Descriptive study with case study approach was applied in this study. The sample of the study was 10thgrade students of SMAN 1 Kembayan academic year of 2016/2017. For collecting data, three instruments were utilized particularly diagnostic test, questionnaire, and interview. Diagnostic test was applied to identify students’ learning difficulty and to ascertain factors that influence students’ learning difficulty, questionnaire and interview were applied. The findings indicate that percentage of students’ difficulty in learning and understanding protist was 58% and it was categorized to be difficult especially on sub-material of chracteristics of animal-likeprotist (70.59%). Students’ learning difficulty was categorized into three levels that are light (level 1), moderate (level 2), and severe (level 3). The average percentage of each category was light (23.53%), moderate (64.71%) and severe (11.76%). Factors that influence students’ difficulty in learning and understanding protist encompass internal factor, specifically 66% and it was categorized to be moderate and external factor, distinctively 55.67% and it was categorized to be moderate as well.Keywords: Learning Difficulties, Diagnostic Test, Protist